2002
DOI: 10.1093/intimm/14.4.367
|View full text |Cite
|
Sign up to set email alerts
|

IFN‐α enhances CD40 ligand‐mediated activation of immature monocyte‐derived dendritic cells

Abstract: Type I IFN are immune modulatory cytokines that are secreted during early stages of infection. Type I IFN bridge the innate and the adaptive immune system in humans and mice. We compared the capacity of type I and II IFN to induce the functional maturation of monocyte-derived dendritic cells (MoDC). Extending our earlier observation that type I IFN promote DC maturation, we report that these cytokines also enhance DC differentiation by augmenting CD40 ligand (CD40L)-induced cytokine secretion by MoDC. Type I I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
83
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 65 publications
16
83
2
1
Order By: Relevance
“…Here we show that immature DC treatment with IFN-a or IFN-c enhanced the PMA-induced NADPH oxidase activity (Fig.1A, B). A surface phenotype analysis by flow cytometry demonstrated that this effect was not consequent to changes of DC maturation stage, as IFN-c and IFN-a did not induce the expression of the maturation markers CD83, CD86 and CD80 (data not shown), as previously reported [14,16,18].…”
Section: Regulation Of Nadph Oxidase Activity By Ifn-a and Ifn-csupporting
confidence: 81%
See 1 more Smart Citation
“…Here we show that immature DC treatment with IFN-a or IFN-c enhanced the PMA-induced NADPH oxidase activity (Fig.1A, B). A surface phenotype analysis by flow cytometry demonstrated that this effect was not consequent to changes of DC maturation stage, as IFN-c and IFN-a did not induce the expression of the maturation markers CD83, CD86 and CD80 (data not shown), as previously reported [14,16,18].…”
Section: Regulation Of Nadph Oxidase Activity By Ifn-a and Ifn-csupporting
confidence: 81%
“…For this purpose, we investigated the effect of cytokines able to modulate DC functions such as IFN-a [13][14][15] and IFN-c [16,17] on NADPH oxidase activity and ability of DC to kill Candida albicans. Moreover, we analyzed the DC receptors involved in Candida uptake and their role in NADPH oxidase activation.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of immature DCs with IFN-a results in the upregulation of surface markers, T-cell stimulatory capacities and migration-related chemokines. 16,17 IFN-c also upregulates IL-12 production, CCR7-driven migration, CD38 expression and activated Th1 cell recruitment. 18 Although a combination of IFN and a TLR3 agonist can generate potent DCs, 19,20 optimization of the combination of these stimuli is needed to produce high-quality DCs that can generate potent cytotoxic T lymphocytes and have the ability to migrate to lymph nodes.…”
Section: Introductionmentioning
confidence: 99%
“…As a member of the TNF-TNFR costimulatory molecule super family, CD40/ CD40L is a key signal for DC maturation into fully functional APCs (14)(15)(16). On the other hand, whether DCs can fully mature depends on their ability to undergo in vivo migration.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that CD40/CD40L is a powerful stimulus in DC function and maturation (14)(15)(16). Previous experiments have demonstrated that maturation of DCs through CD40 signaling can promote a protective CD8 T cell mediated immunity that is independent of CD4 T cell help (17).…”
Section: Introductionmentioning
confidence: 99%